Machinery's handbook a reference book for the mechanical engineer, designer, manufacturing engineer, draftsman, toolmaker, and machinist - Oberg, Erik 1881-; Christopher J. McCauley (Industrial Press, 2012)
Machinery's Handbook has been the most popular reference work in metalworking, design, engineering and manufacturing facilities, and in technical schools and colleges throughout the world for nearly 100 years. The 29th edition of the "bible of the metalworking industries" contains major revisions of existing content, as well as new material on a variety of topics. It is the essential reference for mechanical, manufacturing, and industrial engineers, designers, draftsmen, toolmakers, chinists, engineering and technology students, and the serious home hobbyist. - Publisher